1998
DOI: 10.1021/la980356c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effective Radius of Sterically Stabilized Latex Particles Determined by Small-Angle X-ray Scattering and by Zero Shear Viscosity

Abstract: The influence of an adsorbed layer of a surfactant on the flow behavior of a latex is considered. The system studied consists of a poly(styrene) core latex without chemically bound charges (diameter:  146 nm) and a layer of poly(ethylene oxide) chains (length:  80 ethylene oxide units) affixed to the surface of the particles through adsorption of the surfactant Lutensol AT80 (C16 - 18EO80). Both the core latex as well as the latex covered by surfactant have been studied by small-angle X-ray scattering (SAXS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 21 publications
2
52
0
Order By: Relevance
“…A recent comparison of ⌬ thus obtained with structural data derived from small-angle X-ray scattering showed that both methods agree in good approximation (16). The value of ⌬ may therefore be used as a quantitative measure of the extension of the steric layer on the surface of the particles (cf.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations
“…A recent comparison of ⌬ thus obtained with structural data derived from small-angle X-ray scattering showed that both methods agree in good approximation (16). The value of ⌬ may therefore be used as a quantitative measure of the extension of the steric layer on the surface of the particles (cf.…”
Section: Methodsmentioning
confidence: 91%
“…The poly(styrene) core latex was prepared and purified as described recently (16). The analysis of the core latex showed that the radius a is 72.5 nm (number-average determined by transmission electron microscopy).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the decrease in the droplet diameter, the relative viscosity increases sharply at any given volume fraction of oil nanodroplets. Figure 5 shows six sets of data for nanosuspensions [14,18,[53][54][55]. The type and size of nanoparticles vary from one set to another.…”
Section: Comparison Of Model Predictions With Experimental Data and Dmentioning
confidence: 99%